2008
DOI: 10.1093/hmg/ddn386
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of nesprin-1 produces an Emery Dreifuss muscular dystrophy-like phenotype in mice

Abstract: Mutations in the gene encoding the inner nuclear membrane proteins lamins A and C produce cardiac and skeletal muscle dysfunction referred to as Emery Dreifuss muscular dystrophy. Lamins A and C participate in the LINC complex that, along with the nesprin and SUN proteins, LInk the Nucleoskeleton with the Cytoskeleton. Nesprins 1 and 2 are giant spectrin-repeat containing proteins that have large and small forms. The nesprins contain a transmembrane anchor that tethers to the nuclear membrane followed by a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
185
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(201 citation statements)
references
References 34 publications
16
185
0
Order By: Relevance
“…This report is consistent with the finding that depletion of the nucleoplasmic alpha isoform of LAP2 causes cardiac dysfunction in mice [48]. Mutations and polymorphisms in SYNE1 and SYNE2 genes, which respectively encode the KASH domain proteins nesprin-1 and nesprin-2, have also been reported in patients with muscular dystrophy and cardiomyopathy; disruption of the orthologous genes in mice causes skeletal and cardiac myopathy [49][50][51][52]. A mutation in SYNE1 has also been linked to an autosomal recessive form of arthrogryposis multiplex congenita, a syndrome of congenital joint contractures that results from reduced fetal movement [53].…”
Section: Muscular Dystrophysupporting
confidence: 90%
“…This report is consistent with the finding that depletion of the nucleoplasmic alpha isoform of LAP2 causes cardiac dysfunction in mice [48]. Mutations and polymorphisms in SYNE1 and SYNE2 genes, which respectively encode the KASH domain proteins nesprin-1 and nesprin-2, have also been reported in patients with muscular dystrophy and cardiomyopathy; disruption of the orthologous genes in mice causes skeletal and cardiac myopathy [49][50][51][52]. A mutation in SYNE1 has also been linked to an autosomal recessive form of arthrogryposis multiplex congenita, a syndrome of congenital joint contractures that results from reduced fetal movement [53].…”
Section: Muscular Dystrophysupporting
confidence: 90%
“…KASH-SUN protein complexes also have been implicated in roles related to muscular dystrophies (9,39). The degenerative phenotype may be related to the defects in myonuclear anchorage, including nonsynaptic anchorage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that KASH (Klarsicht/ANC-1/Syne homologue) domain-containing and SUN domain-containing proteins (KASH/SUN proteins) form a complex at the nuclear envelope (NE) for various cellular functions (3)(4)(5)(6). Whereas a mammalian KASH protein has been found to have a critical function in myonuclear anchorage (7)(8)(9), the roles of SUN proteins in this process remain unclear.…”
mentioning
confidence: 99%
“…AHR1b mutation did not affect AHRR induction ( Figure 5A, 2-way ANOVA, P ¼ .043, n ¼ 3). Spectrin repeat-containing nuclear envelope protein 1 (SYNE-1), which encodes a nuclear envelope protein (Muchir and Worman, 2007;Puckelwartz et al, 2009), was induced 6.2-fold by TCDD in wildtype cells. While AHR1b mutation did not affect SYNE-1 mRNA following TCDD treatment, mutation of AHR1a diminished TCDD induction by 74% ( Figure 5B, 2-way ANOVA, P ¼ .0066, n ¼ 3).…”
Section: Target Gene Induction By Tcddmentioning
confidence: 99%